Response of methane production and microbial community to the enrichment of soluble microbial products in goethite-dosed anaerobic reactors. (1st March 2017) - Zhu, Meng-Yang; Peng, Shu-Chuan; Tao, Wei; Wang, Jin; Tang, Ting; Chen, Tian-Hu; Yue, Zheng-Bo
Highlights: Addition of goethite promoted the secretion of SMP in anaerobic digestion reactors. SMP enhanced the overall methane production and generation rate. Goethite and enrichment of SMP influenced the bacterial community significantly. Abstract: Iron oxide facilitated methane production process has recently attracted more and more attention in the worldwide. On the other hand, soluble microbial products (SMPs) was found to play an important role in the wastewater treatment systems. The purpose of this study was to investigate the role of SMPs in the goethite (a typical iron oxide mineral) facilitated methanogenic process, where a dialysis bag was used to enrich the SMPs in the aqueous system. Results showed that both methane yield and production rate were enhanced significantly using the dialysis bag with a molecular weight of 2000 Da compared to the controlled goethite-dosed reactors. Chemical analysis indicated that the increase in contacting time between goethite and microorganisms had insignificant impact on SMPs formation and methane production. It was also found that SMPs especially Flavins secreted from microorganisms could play an important role in the goethite facilitated methane production process. Additionally, enrichment of SMPs not only improved the abundance of electroactive bacteria and but also promoted the growth of aceticlastic methanogenesis.